Mate choice and gene expression signatures associated with nutritional adaptation in the medfly (Ceratitis capitata) - Nash, Will (Sci Rep, 2019)
Evolutionary responses to nutrition are key to understanding host shifts and the resulting potential for reproductive isolation. Experimental evolution has previously been used to describe the responses of the medfly (Ceratitis capitata) to larval diets with different nutritional properties. Within 30 generations this led to divergence in larval development time, egg to adult survival and adaptation in adult body size. Here we used mRNA-seq to identify differences in gene expression patterns in these same populations, using males from the 60(th) generation of nutritional selection. We validated differential expression by using qRT-PCR and found that genes linked to metabolism, oxidative phosphorylation and proteolysis were significantly over-represented among the differentially expressed genes. The results provide the first genome-wide survey of the putative mechanisms underpinning evolved responses to nutritional adaptation. In addition, we tested the hypothesis that nutritional adaptation can alter mating patterns. We found evidence for assortative mating by diet at generation 60, but not 90. Hence, the pattern was variable across generations and there was no evidence overall for any isolating mating divergence between the lines. Overall, the results provide insight into the mechanisms underpinning dietary adaptation and extend our knowledge of which traits represent core responses to nutritional selection.